To the Question of Vitamin D Network in Type 1 Diabetes and Diabetic Nephropathy in Children Nursed in Ukrainian Endocrinology Unit - Ievgeniia Burlaka MD, PhD; I.O. Mityuryayeva MD, PhD (SAGE Publishing, 2022)
Background Vitamin D deficiency is a great problem worldwide. Vitamin D plays an essential role in calcium and bone metabolism. Diabetic nephropathy (DN) is a dangerous kidney-related complication of type 1 diabetes (T1D). Aim of the study To evaluate levels of Vitamin D3 in pediatric patients with T1D and DN; to study the dependence between the Vitamin D level and main clinical and laboratory parameters of the disease, that is, duration, complications episodes, albuminuria levels, glomerular filtration rate (GFR). Material and methods A survey of 72 children with T1D and DN aged 3-17 years was done. Complex examination including conventional methods (physical examination, blood pressure measurement, blood tests, study of urinary sediment, renal ultrasound, etc.) was done for all patients. Data was processed using GraphPad Prism 9.0 Software for Windows (USA, San Diego, CA). p -values <.05 were considered statistically significant. Results Majority of patients from T1D group have normal value of Vitamin D, only 27.7% of children have Vitamin D insufficiency. In contrast, in children from DN group only 16.7% of children have Vitamin D insufficiency and 83.3% have Vitamin D deficiency. Vitamin D serum level negatively correlates with disease duration and albuminuria level in the group with DN. Serum levels of Vitamin D positively correlate with GFR in patients with T1D. Patients with DN who had a duration of T1D for 10 years and more have a higher progression rate to Vitamin D deficiency as compared to those who have a T1D duration of less than 10 years. Conclusions The authors conclude that Vitamin D has a direct relationship with functional disorders with DN, that is, albuminuria, GFR, kidney function. Further investigations of Vitamin D supplementation on different stages of the ND development and progression are needed.